Enhancing farmer learning and adoption of digital extension: A case study report of sorghum and millet farmers in western Kenya - Rickards, Chima Benita; Otieno, Wycliffe; Marenya, Paswel (International Maize and Wheat Improvement Center, 2025)
Agricultural extension services remain critical for bridging the gap between agronomic research and on-farm adoption, yet systemic inefficiencies such as low farmer-to-agent ratios, fragmented knowledge dissemination, and limited accessibility of traditional methods of learning hinder progress. Digital tools offer transformative potential through scalability, real-time interaction, and tailored content delivery. However, their impact is often constrained by poor usability, lack of farmer-centric design, and uneven technological access. In 2023, we piloted a case study in Western Kenya’s Siaya and Busia counties, focusing on sorghum and millet cultivation. The initiative tested a hybrid extension model integrating GeoFarmer, a digital platform, with existing farmer networks. We explored the following research questions: 1. What insights can be drawn from the integration of peer-to-peer learning and two-way knowledge exchange in digital extension platforms? What specific mechanisms and interactions appear to facilitate or hinder knowledge sharing within the examined agricultural community? 2. How do farmers with varying technological backgrounds engage with a Human-Centred Design (HCD) digital platform? Which design elements ease adoption, and what challenges persist in the studied communities? 3. What emerging patterns suggest how digital extension networks can complement traditional in person demonstration methods to support the wider adoption of improved agronomic practices?